Understanding of Pulse Voltage Response Analysis for Degradation in XLPE Cable Using Equivalent Circuit Model - Selvamany, Priya; Varadarajan, Gowri Sree (Journal of electrical engineering & technology, 2022)
Charge (Q–t) characteristic plays a significant role in the insulation undergoing irreversible aging condition of the cable. In this study, the pulse voltage is used as a diagnostic method based on water tree detection. The mechanism of residual charge accompanied in the degraded insulation part using Maxwell–Wagner model by numerical analysis is performed. The charge intensity of healthy and degraded cable for an approximate model of 6.6 kV and the actual model of 66 kV single-core, XLPE insulated cable was considered for simulation analysis. The effect of DC voltage, peak pulse voltage, and a number of pulses on the amount of charge was the subject of our research. The residual charges were increased, which indicates the severely degraded conformity in the tested cable compared with the conventional method. Moreover, the effect of ‘fast pulse’ 4 ns wide and ‘slow pulse’ 1.5 ms wide has been applied and its behavior is quantitatively assessed by simulation test using an actual cable model. Various studies have emphasized using this pulse and identification to seek electrical current signals associated with the water-treeing region. The ‘fast pulse’ signal generates an oscillatory response, contains a 143–585 pC charge, and the ‘slow pulse’ signal generates a non-oscillatory response containing 2.4–9.5 μC charge originate at the water treeing region.